2010
DOI: 10.1128/jcm.01071-10
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Molecular Identification of Pathogenic Yeasts by Pyrosequencing Analysis of 35 Nucleotides of Internal Transcribed Spacer 2

Abstract: Rapid identification of yeast species isolates from clinical samples is particularly important given their innately variable antifungal susceptibility profiles. Here, we have evaluated the utility of pyrosequencing analysis of a portion of the internal transcribed spacer 2 region (ITS2) for identification of pathogenic yeasts. A total of 477 clinical isolates encompassing 43 different fungal species were subjected to pyrosequencing analysis in a strictly blinded study. The molecular identifications produced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
(29 reference statements)
3
37
0
Order By: Relevance
“…We have previously demonstrated that pyrosequencing of 35 bp of a portion of the internal transcribed spacer region 2 (ITS2) is sufficient to robustly identify the vast majority of pathogenic yeasts (27), including genetically closely related isolates within species complexes (28,29). This is also the case for the key species within the C. albicans species complex.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…We have previously demonstrated that pyrosequencing of 35 bp of a portion of the internal transcribed spacer region 2 (ITS2) is sufficient to robustly identify the vast majority of pathogenic yeasts (27), including genetically closely related isolates within species complexes (28,29). This is also the case for the key species within the C. albicans species complex.…”
Section: Resultsmentioning
confidence: 92%
“…All 1,839 test isolates were subjected to pyrosequencing analysis of a portion of ITS2 exactly as described previously (27)(28)(29). For isolates identified by pyrosequencing as C. africana, identity was confirmed by PCR amplification and sequencing of a region of the large subunit gene (LSU) and the internal transcribed spacer 1 (ITS1) region using the primers described previously (30,31) and direct inoculation of PCR products with yeast suspensions as described in reference 32.…”
Section: Methodsmentioning
confidence: 99%
“…Non-Candida yeasts further contribute to an increasingly complicated clinical picture in which more than 150 yeast spp. from Candida and other genera have now been reported from mammalian infections (4,11,15; Mycology Reference Laboratory [MRL], unpublished data).…”
mentioning
confidence: 99%
“…The largest limitation for methods based on PCR is the low sensitivity, as the practice shows only 1-2% of the community can be detected in this way (Macnaughton et al, 1999). Furthermore, fingerprint methods have the bias combined to the fact that amplicons form different species with sequences of similar energetic profile may migrate to the same positions; multiple gene copies with slight sequence differences may give multiple bands for one strain or species; finally some species are phylogeneticaly very similar (Lachance et al, 2003;Janczyk et al, 2006;Borman et al, 2010). The design of probes for direct targeting needs knowledge on the sequence of the target gene and differences between species.…”
Section: Methods For Investigating Biodiversity Of the Yeasts From Gitmentioning
confidence: 99%